Effects of caffeinated chewing gum on ice hockey performance after jet lag intervention: Double-blind crossover trial - Tsai, M.-T.; Shiu, Y.-J.; Ho, C.-C.; Chen, C.-H.; Chiu, C.-H. (Nutrients, 2024)
The purpose of this study was to examine the impact of caffeinated chewing gum on the physical performance of elite ice hockey players after a jet lag intervention. Fourteen national-level (age: 25.2 ± 5.4; height: 176.5 ± 5.3; weight: 78.1 ± 13.4) ice hockey players were tested late at night after a full day awake schedule with jet lag. A randomised, double-blind experimental design was employed in which participants either chewed caffeinated gum (CAF) containing 3 mg/kg caffeine or a caffeine-free placebo gum (PLA) for 10 min prior to undertaking a series of on-ice and off-ice tests. The off-ice tests included grip force, the counter-movement jump (CMJ), and the squat jump (SJ). The on-ice tests included a 35 m sprint, the S-Shape agility test, and the Yo-Yo intermittent recovery test (Yo-Yo IR1 test). The CMJ height (CAF: 47.2 ± 4.4; PL: 45.9 ± 3.5; p = 0.035; Cohen`s d = 0.32) and SJ height (CAF: 46.7 ± 4.1; PL: 44.9 ± 3.8; p = 0.047; Cohen`s d = 0.44) were found to be significantly higher in the CAF than in the PL trial. However, there were no significant differences (p > 0.05) in grip force, as well as in the 35 m sprint, the S-Shape agility test, and the Yo-Yo IR1 test. The present study found that, following a jet lag intervention, although the consumption of caffeinated gum resulted in an increase in vertical jump height, it had no impact on performance in the ice tests. The results of this study may help coaches and athletes consider the need for caffeine supplementation when experiencing jet lag.